Increasing Leg Muscle Power and Leg Muscle Strength with Plyometric Exercise Variations - Yulfiras Thariqi; Oce Wiriawan; Muhammad Muhammad (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
This study aims to determine the effect of the form of plyometric training, namely the Tuck jump, Squad jump, and Basic box jump Exercises to increase leg muscle strength and leg muscle power. The subject of this research is 32 students of SMAN 12 Surabaya. The results of this study, the leg muscle power of group 1 with an average of 609 joules, while the post-test results were 668 joules. Conclusion for group 1 Leg muscle power increased by 10% and strength increased by 3%. The results of group 2 for leg muscle power had an average pretest of 503 joules and an average post-test result of 543 joules. Conclusion of group 2 Leg muscle power increased by 8% and strength increased by 3%. The results of group 3 for leg muscle power had an average pre-test of 602 joules and an average post-test result of 645 joules. Conclusions for group 3 leg muscle power increased by 7% and strength increased by 3%. In conclusion, the results of this study Group 1, group 2, and Group 3 exercises affect leg muscle strength and leg muscle power, for leg muscle strength the increases are all the same and for leg muscle power which has a big influence, namely group 1 with the tuck jump exercise for strength and leg muscle power.